THE EFFECTS OF HUMAN TRAFFICKING IN WINGATE’S BEFORE WE WERE YOURS - Jechinta Pinontoan; Ceisy N Wuntu; Sanerita T. Olii (Program Studi Pendidikan Bahasa Inggris, 2023)
This research is to reveal the effect of human trafficking portrayed in Wingate’s Before We Were Yours. This research is classified as qualitative research. Literary theory of objective formulated by M.H. Abrams will frame the analysis of the data. This literary theory regards a work of literature is built from the internal relation of aspects found in a work of literature, the connection, the interrelation of internal aspects of a work of literature is really essential for the meaning behind the work. The implementation is that the data applied are in the novel. The result of the discussion is synthesizised from the interrelation of the elements in the work or intrinsic data. It is found that human trafficking brings emotionally suffered and physically suffered. The trafficking is forced by a power, a business in which it is because of the unremovable reason, that is money. And it is also because of the money the ‘evil’ execution of human trafficking is done. Avoiding the society norms and values, can be a source of evil including human trafficking that can cause human suffering.